2023
DOI: 10.1021/acs.jmedchem.3c01716
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Translocator Protein (18 kDa) in Cardiac Diseases: State of the Art and Future Opportunities

Emma Baglini,
Valeria Poggetti,
Chiara Cavallini
et al.

Abstract: Mitochondria dysfunctions are typical hallmarks of cardiac disorders (CDs). The multiple tasks of this energy-producing organelle are well documented, but its pathophysiologic involvement in several manifestations of heart diseases, such as altered electromechanical coupling, excitability, and arrhythmias, is still under investigation. The human 18 kDa translocator protein (TSPO) is a protein located on the outer mitochondrial membrane whose expression is altered in different pathological conditions, including… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 152 publications
(345 reference statements)
0
0
0
Order By: Relevance
“…Our studies of human cardiomyocytes link HIF-1α activation with TSPO, which has been suggested to function in myriad processes, including intracellular cholesterol transport and steroid hormone biosynthesis. 82 We speculate that some of the well-established responses of cardiomyocytes to hypoxia in developmental, physiological, and pathophysiological contexts 66,76,104,105 involve TSPO. First, TSPO in cardiomyocytes has been reported to influence heart rate and muscle contractile force by modulating voltage-dependent Ca 2+ channels.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Our studies of human cardiomyocytes link HIF-1α activation with TSPO, which has been suggested to function in myriad processes, including intracellular cholesterol transport and steroid hormone biosynthesis. 82 We speculate that some of the well-established responses of cardiomyocytes to hypoxia in developmental, physiological, and pathophysiological contexts 66,76,104,105 involve TSPO. First, TSPO in cardiomyocytes has been reported to influence heart rate and muscle contractile force by modulating voltage-dependent Ca 2+ channels.…”
Section: Discussionmentioning
confidence: 90%
“…In particular, these mammalian homologs modulate both the heart rate and the contractility of cardiomyocytes. 6466 In this study, we asked if tspo-1 functions in the hypoxia response in muscle cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation